2016
DOI: 10.12943/cnr.2015.00059
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Responses to Tritium Exposure in Rainbow Trout: Hto- And Obt-Spiked Feed Exposure Experiments

Abstract: Biological effects were evaluated in rainbow trout (Oncorhynchus mykiss) exposed to tritiated water (HTO) or food spiked with organically bound tritium (OBT). An HTO exposure study was conducted using a tritium activity concentration of 7000 Bq/L, and an OBT exposure study was conducted using a tritium activity concentration of 30 000 Bq/L. Following 140 days of in vivo HTO exposure, liver, heart, spleen, kidney, and brain cells did not show statistically significant differences in viability; kidney, liver, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…Optimisation of the gamma-H2AX assay in gill cells was performed using a [70], cell nuclei were located with an appropriate DAPI filter, and a FITC filter set for the FITC signal of the γ-H2AX primary antibody. All slides, including procedural blanks were coded and scored at random.…”
Section: Induction Of γ-H2ax Focimentioning
confidence: 99%
“…Optimisation of the gamma-H2AX assay in gill cells was performed using a [70], cell nuclei were located with an appropriate DAPI filter, and a FITC filter set for the FITC signal of the γ-H2AX primary antibody. All slides, including procedural blanks were coded and scored at random.…”
Section: Induction Of γ-H2ax Focimentioning
confidence: 99%
“…It is indeed interesting that fatty acid changes previously reported in tissues after in vivo radiation and tritium exposure of amphibians and fish also pointed out an increased MUFA content, thus suggesting that this aspect can be further developed as a specific radiation response (Audette‐Stuart et al., ; Festarini et al., ). Moreover, the present data on the EPA loss in the hippocampus of exposed mice suggest further development in view of the reported model of EPA supplementation that activated the interleukin‐1β‐induced cell signaling in the hippocampus of rats exposed to gamma irradiation (Lynch et al., ).…”
Section: Discussionmentioning
confidence: 94%
“…Some of us have previously shown that fatty acid changes are sensitive markers of radiation exposure in amphibians (Audette‐Stuart et al., ), whereas in trout exposed to food spiked with tritium, both liver and muscle tissues were found to change their fatty acids significantly compared to controls. Under these conditions, no significant differences in DNA strand break repair activity were found (Festarini et al., ). Those experiments showed that PUFA consumption was not occurring, but instead a remodeling response of the phospholipid fatty acid moieties with an increase in unsaturated components was taking place.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations